Metoda Punktów Kinetycznych - Wolski, Kazimierz (Engineering Transactions, 1955)
The «method of kinetic points» (or mass points kinetically equivalent to the given rigid system of masses) has been applied so far to particular cases only. It is the author's aim to expand in this paper, a new branch of dynamics comprising certain general principles of a method for solving more difficult problems of a practical nature, for instance the spatial motion of a solid of arbitrary mass distribution.The determination of kinetic points is based on necessary and sufficient conditions of common centre of mass and common central ellipsoid of inertia of the solid and its kinetic points.In order to determine the kinetic points for solids encountered in engineering problems, usually composed of simple geometric figures, a table of kinetic points for such figures is given. In order to generalize this to oblique figures a theorem is demonstrated, according to which all kinetic points of a solid are displaced under affine transformation, as points pertaining to the solid. In other words, the co-ordinates of kinetic points in the system of co-ordinates transformed jointly with the solid behave as invariants.The method of kinetic points is particularly suitable when used together with the graphical method. It is likely, therefore, to find a wider application in engineering practice.